China's flexibility challenge in achieving carbon neutrality by 2060. (April 2022) - Li, Jianglong; Ho, Mun Sing; Xie, Chunping; Stern, Nicholas
Abstract: China, with a heavy dependence on coal power, has announced a clear goal of carbon neutrality by 2060. Electrification of final energy use and high penetration of renewable energy are essential to achieve this. The resulting growth of intermittent renewables and changes in demand curve profiles require greater flexibility in the power system for real-time balancing – greater ability of generators and consumers to ramp up and down. However, the plan and market system with regulated prices makes this challenging. We discuss the options to improve flexibility, including 1) increasing supply-side flexibility, through retrofitting existing power plants to boost their responsiveness; 2) promoting flexibility from power grids, through building an efficient power grid with inter-provincial and inter-regional transmission capacity to balance spatial mismatch, given that China has a vast territory; 3) encouraging demand flexibility, through demand-response measures to enable demand shifting over time and space to address fluctuations in renewable energy generation; and 4) providing flexibility from energy storage. We consider policies to achieve this, in particular, power market reforms to unlock the flexibility potential of these sources. Regulated electricity prices and lack of auxiliary services markets are major obstacles and we discuss how markets in other countries provide lessons in providing incentives for a more flexible system. Highlights: Carbon neutrality requires electrification and intermittent renewables. Discuss options to improve flexibility in power system with high renewables. Attention to technology and market policies in system with regulated prices and quotas. Exploring how markets in other countries may provide lessons for China.